The Church of God in Jesus Christ : a Catholic ecclesiology - Kereszty, Roch A. (The Catholic University of America Press, 2019)
"This book establishes three aspects of the mystery of the Church: that the Church is (1) the people of God, chosen for the salvation of the world in Christ; (2) the virginal Bride who becomes one Body and one Spirit by Christ; and (3) the Mother through the Holy Spirit of all believers. The author first traces the history of relevant teachings from the Old Testament up to the present, and then provides a systematic ecclesiology"--